Heparin Resistance, Thromboplastin Generation and Glass Activation - Gormsen, Johs (Thrombosis and Haemostasis, 1961)
Simultaneous studies of the heparin resistance, thromboplastin generation, the partial thromboplastin time and recalcification time in normal control persons and in patients with increased heparin resistance, before and after activation with celite, appear to indicate that heparin resistance is very dependent to a factor or factor systems bound to celite.